Perancangan Ilustrasi Buku “Patah Untuk Tumbuh” - Arief Hidayat Chaniago; Heldi Heldi (Jurnal Kajian dan Penelitian Umum, 2023)
Heartbreak is a mental condition and social problem associated with teenagers who are failing in a romantic relationship. Heartbreak can occur in various circumstances, the end of a love story can be triggered by the end of a romantic relationship with a partner. This issue was raised as a paper by Apriyandisi under the pen name @berbagi_rasa. With the title "Broken to Grow". What's interesting about this book is how Apriyandisi is very good at packing every content in this book. This book is very light and good for those who want to use the book as a motivation to move forward. The aim of this final work is to produce a book that is more effective, informative and communicative and more attractive to the target audience. The method in this design uses the 4-D method. This method is used to produce an Illustrated Book media product. The product developed is then tested for its usefulness by testing validity and product testing to find out how much the reader's motivation has increased. after reading this book the data analysis technique with the 5W + 1H technique is to make it easier to find solutions to problems. This book is designed with illustrations, layout, typography, colors. This illustration book is the main media and this design has supporting media such as x banners, posters, notebooks, tumblers, stickers, and pins.